New Generation Functional Testing Desk for Control Cabinet of Locomotive - 李鹏; 罗继光; 陈明奎; 苏理 (机车电传动)
Equipment for providing system-level functional testing to locomotive control cabinet was introduced. The functions, component of system and characteristic of software/hardware designing were expounded. This equipment has passed the FAI with high improvement of accuracy and response speed.